Cutaneous side effects of inhibitors of the RAS/RAF/MEK/ERK signalling pathway and their management. (28th April 2012) - Manousaridis, I.; Mavridou, S.; Goerdt, S.; Leverkus, M.; Utikal, J.
Abstract Mutations in genes encoding for proteins along the RAS‐RAF‐MEK‐ERK pathway have been detected in a variety of tumor entities, including malignant melanoma, thyroid, colonic and ovarian carcinomas, and some sarcomas. Thus, a number of inhibitors of this pathway have been developed, whose antitumor potential is currently being assessed in different clinical trials. Up to now one drug of this category (vemurafenib) has been approved by the FDA and the European Commission for late‐stage melanoma. Although these new targeted anticancer therapies are generally considered to be safe and well tolerated, certain toxicities have been attributed to them, with cutaneous side effects being perhaps the most frequent amongst them. Based on results of clinical trials and on case series, a distinct profile of cutaneous toxicity has been observed, which is similar to that of EGFR and multikinase inhibitors. As exanthema, palmar‐plantar erythrodysesthesia syndrome, hyperkeratosis, xerosis, pruritus, photosensitivity, and paronychia, can be controlled in most cases with common conservative modalities, special attention should be given to the early detection of epithelial skin tumors (mainly keratoakanthomas) that can be induced during therapy with these agents. This report reviews all current published data on cutaneous side effects of RAS‐RAF‐MEK‐ERK pathway inhibitors, and attempts to provide the clinician with clear hints for their management.